It Won't Be Easy : An Exceedingly Honest (and Slightly Unprofessional) Love Letter to Teaching - Rademacher, Tom, 1981- (Book collections on Project MUSE., 2017)
Tom Rademacher wishes someone had handed him this sort of book along with his teaching degree: a clear-eyed, frank, boots-on-the ground account of what he was getting into. But first he had to write it. And as 2014?s Minnesota Teacher of the Year, Rademacher knows what he?s talking about. Less a how-to manual than a tribute to an impossible and impossibly rewarding profession, It Won?t Be EasyIt Won?t Be Easy is mercifully short on jargon and long on practical wisdom, accessible to anyone?teacher, student, parent, pundit?who is interested in a behind-the-curtain look at teaching and willing to understand that, while there are no simple answers, there is power in learning to ask the right questions.